The Training of BUMNag's Financial Statement Understanding and Analysis - Riwayadi; Husna Roza (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Community services aim to build the competency of the financial statement analysis for the decision makers of BUMNag Anrila Sejahtera so that they can make better strategic decision making to develop BUMNag Anrila Sejahtera’s business. Most decision makers are non-accountants who should be able to analyze the financial statements. With this competency, they can evaluate BUMNag’s financial performance and formulate strategies to develop BUMNag’s business. The community services method covers Focus Group Discussion (FGD), Observation, and training. FGD is performed by inviting Wali Nagari, BAMUS, Wali Jorong, the management of BUMNag Anrila Sejahtera, and other key stakeholders. Observation is performed by reviewing the accounting systems developed by BUMNag Anrila Sejahtera. There are two stages of training: introduction to BUMNag financial statements, and analysis of BUMNag Anrila Sejahtera’s financial statements. The survey found that the training participants were highly satisfied and gained more insight and knowledge. Further, observation also found the weaknesses of accounting systems for financial reporting. BUMNag Anrila Sejahtera expected the expert assistance to develop better accounting information systems and other aspects, such as manufacturing the quality Madu Galo-Galo, and marketing the products.